Evaluating the Capacity of Existing Stormwater Drainage System in Kapan, Kathmandu via SWMM Mode - Pokhrel, Subidha; Koirala, Devendra; Nepal, Prashan; Pande, Pukar; Shah, Ronisa; Khanal, Sabina; Ban, Jeevan Kumar (Kathford Journal of Engineering and Management, 2023)
Overflowing drainage systems in the Nepalese cities are the most significant issue due to unplanned urban expansion and inadequate drainage networks. As the city's drainage networks are not designed to handle the extra runoff from catastrophic flooding incidents, flash floods typically occur during short-duration, and high-intensity rainstorm storms frequently. In the vicinity of Kapan, Kathmandu, and many other Nepalese cities, particularly during the rainy season, roads are seen changing into the streams. This study employs a hydrological analysis model to examine the storm water drainage system existing currently in the Kapan area. Being the EPA Storm Water Management Model (SWMM) physically based, deterministic type that simulates the inflows, outflows, and storages of water within a sub-catchment efficiently, it is chosen here mainly to model the catchments specifically. Though it has not been employed frequently in the context of Nepal, despite its popularity in the industrialized countries such as United States of America for the proper management of the storm water, the SWMM is particularly employed here to model the catchments due to its publicly available, easy to obtain, simple data input parameters, and simple processing steps in compared to other relatively more expensive yet sophisticated models. The catchment's overall area of 360.57 hectares was at first separated into the 86 sub catchments using the SWMM based on its surface elevation and existing drainage network, and the attributes of each sub-catchment were then assigned accordingly. After the proper identification of the sub-catchments, the runoff from the relevant sub-catchments was routed to the respective nodes, and finally to the outlet via conduits. In the current study, the drain system (Combined Sewer line) is given along the center of the road network. The storm network are represented by junctions, conduits, and outfalls. The longitudinal and velocity profiles of the drain were obtained. The critical runoff and capacity of existing drains were determined, as well as their validation with discharge derived using the rational technique. With the runoff generated during peak rainfall 45.08 mm/hr., the Kapan area's existing drainage system was found to be insufficient. This study suggests that the SWMM would be the most effective model to be employed for predicting the sudden surface runoff and for prior managing of the storm water, particularly in Kathmandu and other vulnerable parts of main cities in Nepal, where overflow has caused serious problems during rainfall.